A Million Element Integral Field Unit (MEIFU) - Morris, S; Content, R; Sharples, R; Bower, R; Davies, R; Baugh, C (2001)
We describe an instrument concept that will provide simultaneous spectra for a million spatial samples on the sky. With the proposed field of view and spectral resolution, it will be able to measure redshifts and line strengths for around 2-4000 z~3-7 galaxies in a 16 night campaign. The main science driver is to obtain a complete census of the star formation properties of galaxies with 2.5